How do Explanations Justify? An Extended Scheme for Inference to the Best (Causal) Explanation - Bodlović, Petar; Lewiński, Marcin (Informal Logic)

(untitled) (Informal Logic, 2024)
The paper presents an extended scheme for the inference to the best explanation (IBE). The scheme precisely treats the epistemic modifiers (“hypothetically,” “plausibly,” “presumably”) of the inference, acknowledges its contrastive nature, clarifies the logical support between premises and conclusions (linked, convergent, and serial support), and introduces additional premises essential for inferring justified conclusions (especially those related to causal explanations and more demanding standards of proof). Overall, it advances the existing schemes for IBE in argumentation theory and treats IBE as a par excellence argumentative, rather than explanatory, form of reasoning.